2021
DOI: 10.1002/ejic.202100013
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Linked Polymeric Micelles as Catalytic Nanoreactors

Abstract: Cross-linked micelles have emerged as promising catalyst supports over the past two decades due to their improved structural stability, chemical diversity in multiple domains, and catalyst recovery compared to their uncross-linked analogues. We highlight the different physicochemical properties that arise by cross-linking the shell or core-domain and the subsequent impact on catalysis. Both, shell cross-linked micelles (SCMs) and core cross-linked micelles (CCMs) were initially designed to include one catalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 83 publications
0
26
0
Order By: Relevance
“…Crosslinking, which may be realized either on the shell, in the core, or at an intermediate corona level for multiblock copolymer micelles, removes the dynamic equilibrium between the micellar objects and the free arm constituents, thus improving properties such as drug loading capacity, stability, and confinement in the aqueous medium. [1][2][3][4][5][6][7][8] Controlled radical polymerizations are compatible with water as reaction medium, in addition to being applicable to a wide range of monomers and can be implemented under less stringent conditions relative to the non-radical methods. Among the various possible techniques, reversible addition-fragmentation chain-transfer (RAFT) polymerization has been very successful, 9,10 particularly when combined with "polymerization-induced self-assembly" (PISA), [11][12][13][14][15] directly leading to crosslinked particles in a one-pot process in water.…”
Section: Introductionmentioning
confidence: 99%
“…Crosslinking, which may be realized either on the shell, in the core, or at an intermediate corona level for multiblock copolymer micelles, removes the dynamic equilibrium between the micellar objects and the free arm constituents, thus improving properties such as drug loading capacity, stability, and confinement in the aqueous medium. [1][2][3][4][5][6][7][8] Controlled radical polymerizations are compatible with water as reaction medium, in addition to being applicable to a wide range of monomers and can be implemented under less stringent conditions relative to the non-radical methods. Among the various possible techniques, reversible addition-fragmentation chain-transfer (RAFT) polymerization has been very successful, 9,10 particularly when combined with "polymerization-induced self-assembly" (PISA), [11][12][13][14][15] directly leading to crosslinked particles in a one-pot process in water.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, for hydrogenation, the catalytic performance was dependent on the size of the substrate. Whereas 3-buten-2-ol and 2-methyl-3-buten-2-ol did not react, hydrogenation of 1-hexene was observed under the same conditions, with 82% yield [ 96 , 97 ]. Clusters (0.7 nm, approximately seven atoms) of Pd atoms could also be incorporated into shell-crosslinked micelles using ligand exchange with Pd(PPh 3 ) 4 .…”
Section: Block Copolymer Micellesmentioning
confidence: 99%
“…Heck reactions could also be performed at low Pd loadings (0.001 mol%). Low leaching confirmed that the Pd was encapsulated within the hydrophobic core of the micelles [ 97 ].…”
Section: Block Copolymer Micellesmentioning
confidence: 99%
See 2 more Smart Citations